Effective ratner theorem for SL (2, R) ⋉R2 and gaps in √n modulo 1 - Timothy Browning; Vinogradov, Ilya (Journal of the London Mathematical Society)
Let G = SL(2, R) ⋉R2 and Γ = SL(2, Z) ⋉Z2. Building on recent work of Strömbergsson, we prove a rate of equidistribution for the orbits of a certain one-dimensional unipotent flow of Γ\G, which projects to a closed horocycle in the unit tangent bundle to the modular surface. We use this to answer a question of Elkies and McMullen by making effective the convergence of the gap distribution of √n mod 1.

The genomic basis of adaptation to the fitness cost of rifampicin resistance in Pseudomonas aeruginosa - Qi, Qin; Toll Riera, Macarena; Heilbron, Karl; Preston, Gail; Maclean, R Craig (Proceedings of the Royal Society of London Series B Biological Sciences)
Antibiotic resistance carries a fitness cost that must be overcome in order for resistance to persist over the long term. Compensatory mutations that recover the functional defects associated with resistance mutations have been argued to play a key role in overcoming the cost of resistance, but compensatory mutations are expected to be rare relative to generally beneficial mutations that increase fitness, irrespective of antibiotic resistance. Given this asymmetry, population genetics theory predicts that populations should adapt by compensatory mutations when the cost of resistance is large, whereas generally beneficial mutations should drive adaptation when the cost of resistance is small. We tested this prediction by determining the genomic mechanisms underpinning adaptation to antibiotic-free conditions in populations of the pathogenic bacterium Pseudomonas aeruginosa that carry costly antibiotic resistance mutations. Whole-genome sequencing revealed that populations founded by high-cost rifampicin-resistant mutants adapted via compensatory mutations in three genes of the RNA polymerase core enzyme, whereas populations founded by low-cost mutants adapted by generally beneficial mutations, predominantly in the quorum-sensing transcriptional regulator gene lasR. Even though the importance of compensatory evolution in maintaining resistance has been widely recognized, our study shows that the roles of general adaptation in maintaining resistance should not be underestimated and highlights the need to understand how selection at other sites in the genome influences the dynamics of resistance alleles in clinical settings.

Structure preserving signatures and commitments to group elements - Abe, Masayuki; Fuchsbauer, Georg; Groth, Jens; Haralambiev, Kristiyan; Ohkubo, Miyako (Journal of Cryptology)
A modular approach to constructing cryptographic protocols leads to simple designs but often inefficient instantiations. On the other hand, ad hoc constructions may yield efficient protocols at the cost of losing conceptual simplicity. We suggest a new design paradigm, structure-preserving cryptography, that provides a way to construct modular protocols with reasonable efficiency while retaining conceptual simplicity. A cryptographic scheme over a bilinear group is called structure-preserving if its public inputs and outputs consist of elements from the bilinear groups and their consistency can be verified by evaluating pairing-product equations. As structure-preserving schemes smoothly interoperate with each other, they are useful as building blocks in modular design of cryptographic applications. This paper introduces structure-preserving commitment and signature schemes over bilinear groups with several desirable properties. The commitment schemes include homomorphic, trapdoor and length-reducing commitments to group elements, and the structure-preserving signature schemes are the first ones that yield constant-size signatures on multiple group elements. A structure-preserving signature scheme is called automorphic if the public keys lie in the message space, which cannot be achieved by compressing inputs via a cryptographic hash function, as this would destroy the mathematical structure we are trying to preserve. Automorphic signatures can be used for building certification chains underlying privacy-preserving protocols. Among a vast number of applications of structure-preserving protocols, we present an efficient round-optimal blind-signature scheme and a group signature scheme with an efficient and concurrently secure protocol for enrolling new members.

Quantitative analysis of dendritic cell haptotaxis - Schwarz, Jan; Sixt, Michael K (Methods in Enzymology)
Chemokines are the main guidance cues directing leukocyte migration. Opposed to early assumptions, chemokines do not necessarily act as soluble cues but are often immobilized within tissues, e.g., dendritic cell migration toward lymphatic vessels is guided by a haptotactic gradient of the chemokine CCL21. Controlled assay systems to quantitatively study haptotaxis in vitro are still missing. In this chapter, we describe an in vitro haptotaxis assay optimized for the unique properties of dendritic cells. The chemokine CCL21 is immobilized in a bioactive state, using laser-assisted protein adsorption by photobleaching. The cells follow this immobilized CCL21 gradient in a haptotaxis chamber, which provides three dimensionally confined migration conditions.

Polysialylation controls dendritic cell trafficking by regulating chemokine recognition - Kiermaier, Eva; Moussion, Christine; Veldkamp, Christopher; Gerardy Schahn, Rita; De Vries, Ingrid; Williams, Larry; Chaffee, Gary; Phillips, Andrew; Freiberger, Friedrich; Imre, Richard; Taleski, Deni; Payne, Richard; et al. (Science)
The addition of polysialic acid to N- and/or O-linked glycans, referred to as polysialylation, is a rare posttranslational modification that is mainly known to control the developmental plasticity of the nervous system. Here we show that CCR7, the central chemokine receptor controlling immune cell trafficking to secondary lymphatic organs, carries polysialic acid. This modification is essential for the recognition of the CCR7 ligand CCL21. As a consequence, dendritic cell trafficking is abrogated in polysialyltransferase-deficient mice, manifesting as disturbed lymph node homeostasis and unresponsiveness to inflammatory stimuli. Structure-function analysis of chemokine-receptor interactions reveals that CCL21 adopts an autoinhibited conformation, which is released upon interaction with polysialic acid. Thus, we describe a glycosylation-mediated immune cell trafficking disorder and its mechanistic basis.

Anderson transition at 2 dimensional growth rate on antitrees and spectral theory for operators with one propagating channel - Sadel, Christian (Annales Henri Poincare)
We show that the Anderson model has a transition from localization to delocalization at exactly 2 dimensional growth rate on antitrees with normalized edge weights which are certain discrete graphs. The kinetic part has a one-dimensional structure allowing a description through transfer matrices which involve some Schur complement. For such operators we introduce the notion of having one propagating channel and extend theorems from the theory of one-dimensional Jacobi operators that relate the behavior of transfer matrices with the spectrum. These theorems are then applied to the considered model. In essence, in a certain energy region the kinetic part averages the random potentials along shells and the transfer matrices behave similar as for a one-dimensional operator with random potential of decaying variance. At d dimensional growth for d>2 this effective decay is strong enough to obtain absolutely continuous spectrum, whereas for some uniform d dimensional growth with d<2 one has pure point spectrum in this energy region. At exactly uniform 2 dimensional growth also some singular continuous spectrum appears, at least at small disorder. As a corollary we also obtain a change from singular spectrum (d≤2) to absolutely continuous spectrum (d≥3) for random operators of the type rΔdr+λ on ℤd, where r is an orthogonal radial projection, Δd the discrete adjacency operator (Laplacian) on ℤd and λ a random potential.

CSP for binary conservative relational structures - Kazda, Alexandr (Algebra Universalis)
We prove that whenever A is a 3-conservative relational structure with only binary and unary relations,then the algebra of polymorphisms of A either has no Taylor operation (i.e.,CSP(A)is NP-complete),or it generates an SD(∧) variety (i.e.,CSP(A)has bounded width).

Modeling Alzheimer's disease with human induced pluripotent stem (iPS) cells - Mungenast, Alison; Siegert, Sandra; Tsai, Li (Molecular and Cellular Neuroscience)
In the last decade, induced pluripotent stem (iPS) cells have revolutionized the utility of human in vitro models of neurological disease. The iPS-derived and differentiated cells allow researchers to study the impact of a distinct cell type in health and disease as well as performing therapeutic drug screens on a human genetic background. In particular, clinical trials for Alzheimer's disease (AD) have been often failing. Two of the potential reasons are first, the species gap involved in proceeding from initial discoveries in rodent models to human studies, and second, an unsatisfying patient stratification, meaning subgrouping patients based on the disease severity due to the lack of phenotypic and genetic markers. iPS cells overcome this obstacles and will improve our understanding of disease subtypes in AD. They allow researchers conducting in depth characterization of neural cells from both familial and sporadic AD patients as well as preclinical screens on human cells. In this review, we briefly outline the status quo of iPS cell research in neurological diseases along with the general advantages and pitfalls of these models. We summarize how genome-editing techniques such as CRISPR/Cas will allow researchers to reduce the problem of genomic variability inherent to human studies, followed by recent iPS cell studies relevant to AD. We then focus on current techniques for the differentiation of iPS cells into neural cell types that are relevant to AD research. Finally, we discuss how the generation of three-dimensional cell culture systems will be important for understanding AD phenotypes in a complex cellular milieu, and how both two- and three-dimensional iPS cell models can provide platforms for drug discovery and translational studies into the treatment of AD.

Intrinsic membrane properties determine hippocampal differential firing pattern in vivo in anesthetized rats - Kowalski, Janina; Gan, Jian; Jonas, Peter M; Pernia-Andrade, Alejandro (Hippocampus)
The hippocampus plays a key role in learning and memory. Previous studies suggested that the main types of principal neurons, dentate gyrus granule cells (GCs), CA3 pyramidal neurons, and CA1 pyramidal neurons, differ in their activity pattern, with sparse firing in GCs and more frequent firing in CA3 and CA1 pyramidal neurons. It has been assumed but never shown that such different activity may be caused by differential synaptic excitation. To test this hypothesis, we performed high-resolution whole-cell patch-clamp recordings in anesthetized rats in vivo. In contrast to previous in vitro data, both CA3 and CA1 pyramidal neurons fired action potentials spontaneously, with a frequency of ∼3–6 Hz, whereas GCs were silent. Furthermore, both CA3 and CA1 cells primarily fired in bursts. To determine the underlying mechanisms, we quantitatively assessed the frequency of spontaneous excitatory synaptic input, the passive membrane properties, and the active membrane characteristics. Surprisingly, GCs showed comparable synaptic excitation to CA3 and CA1 cells and the highest ratio of excitation versus hyperpolarizing inhibition. Thus, differential synaptic excitation is not responsible for differences in firing. Moreover, the three types of hippocampal neurons markedly differed in their passive properties. While GCs showed the most negative membrane potential, CA3 pyramidal neurons had the highest input resistance and the slowest membrane time constant. The three types of neurons also differed in the active membrane characteristics. GCs showed the highest action potential threshold, but displayed the largest gain of the input-output curves. In conclusion, our results reveal that differential firing of the three main types of hippocampal principal neurons in vivo is not primarily caused by differences in the characteristics of the synaptic input, but by the distinct properties of synaptic integration and input-output transformation.

On the discrepancy of jittered sampling - Pausinger, Florian; Steinerberger, Stefan (Journal of Complexity)
We study the discrepancy of jittered sampling sets: such a set P⊂ [0,1]d is generated for fixed m∈ℕ by partitioning [0,1]d into md axis aligned cubes of equal measure and placing a random point inside each of the N=md cubes. We prove that, for N sufficiently large, 1/10 d/N1/2+1/2d ≤EDN∗(P)≤ √d(log N) 1/2/N1/2+1/2d, where the upper bound with an unspecified constant Cd was proven earlier by Beck. Our proof makes crucial use of the sharp Dvoretzky-Kiefer-Wolfowitz inequality and a suitably taylored Bernstein inequality; we have reasons to believe that the upper bound has the sharp scaling in N. Additional heuristics suggest that jittered sampling should be able to improve known bounds on the inverse of the star-discrepancy in the regime N≳dd. We also prove a partition principle showing that every partition of [0,1]d combined with a jittered sampling construction gives rise to a set whose expected squared L2-discrepancy is smaller than that of purely random points.

The external field dependence of the BCS critical temperature - Frank, Rupert; Hainzl, Christian; Seiringer, Robert; Solovej, Jan (Communications in Mathematical Physics)
We consider the Bardeen–Cooper–Schrieffer free energy functional for particles interacting via a two-body potential on a microscopic scale and in the presence of weak external fields varying on a macroscopic scale. We study the influence of the external fields on the critical temperature. We show that in the limit where the ratio between the microscopic and macroscopic scale tends to zero, the next to leading order of the critical temperature is determined by the lowest eigenvalue of the linearization of the Ginzburg–Landau equation.

Fractional Hardy–Lieb–Thirring and related Inequalities for interacting systems - Lundholm, Douglas; Nam, Phan; Portmann, Fabian (Archive for Rational Mechanics and Analysis)
We prove analogues of the Lieb–Thirring and Hardy–Lieb–Thirring inequalities for many-body quantum systems with fractional kinetic operators and homogeneous interaction potentials, where no anti-symmetry on the wave functions is assumed. These many-body inequalities imply interesting one-body interpolation inequalities, and we show that the corresponding one- and many-body inequalities are actually equivalent in certain cases.

Spread of pedigree versus genetic ancestry in spatially distributed populations - Kelleher, Jerome; Etheridge, Alison; Véber, Amandine; Barton, Nicholas H (Theoretical Population Biology)
Ancestral processes are fundamental to modern population genetics and spatial structure has been the subject of intense interest for many years. Despite this interest, almost nothing is known about the distribution of the locations of pedigree or genetic ancestors. Using both spatially continuous and stepping-stone models, we show that the distribution of pedigree ancestors approaches a travelling wave, for which we develop two alternative approximations. The speed and width of the wave are sensitive to the local details of the model. After a short time, genetic ancestors spread far more slowly than pedigree ancestors, ultimately diffusing out with radius ## rather than spreading at constant speed. In contrast to the wave of pedigree ancestors, the spread of genetic ancestry is insensitive to the local details of the models.

A forward genetic screen for new regulators of auxin mediated degradation of auxin transport proteins in Arabidopsis thaliana - Zemová, Radka; Zwiewka, Marta; Bielach, Agnieszka; Robert, Hélène; Friml, Jirí (Journal of Plant Growth Regulation)
The plant hormone auxin (indole-3-acetic acid) is a major regulator of plant growth and development including embryo and root patterning, lateral organ formation and growth responses to environmental stimuli. Auxin is directionally transported from cell to cell by the action of specific auxin influx [AUXIN-RESISTANT1 (AUX1)] and efflux [PIN-FORMED (PIN)] transport regulators, whose polar, subcellular localizations are aligned with the direction of the auxin flow. Auxin itself regulates its own transport by modulation of the expression and subcellular localization of the auxin transporters. Increased auxin levels promote the transcription of PIN2 and AUX1 genes as well as stabilize PIN proteins at the plasma membrane, whereas prolonged auxin exposure increases the turnover of PIN proteins and their degradation in the vacuole. In this study, we applied a forward genetic approach, to identify molecular components playing a role in the auxin-mediated degradation. We generated EMS-mutagenized Arabidopsis PIN2::PIN2:GFP, AUX1::AUX1:YFP eir1aux1 populations and designed a screen for mutants with persistently strong fluorescent signals of the tagged PIN2 and AUX1 after prolonged treatment with the synthetic auxin 2,4-dichlorophenoxyacetic acid (2,4-D). This approach yielded novel auxin degradation mutants defective in trafficking and degradation of PIN2 and AUX1 proteins and established a role for auxin-mediated degradation in plant development.

New realizations of somewhere statistically binding hashing and positional accumulators - Okamoto, Tatsuaki; Pietrzak, Krzysztof Z; Waters, Brent; Wichs, Daniel
A somewhere statistically binding (SSB) hash, introduced by Hubáček and Wichs (ITCS ’15), can be used to hash a long string x to a short digest y = H hk (x) using a public hashing-key hk. Furthermore, there is a way to set up the hash key hk to make it statistically binding on some arbitrary hidden position i, meaning that: (1) the digest y completely determines the i’th bit (or symbol) of x so that all pre-images of y have the same value in the i’th position, (2) it is computationally infeasible to distinguish the position i on which hk is statistically binding from any other position i’. Lastly, the hash should have a local opening property analogous to Merkle-Tree hashing, meaning that given x and y = H hk (x) it should be possible to create a short proof π that certifies the value of the i’th bit (or symbol) of x without having to provide the entire input x. A similar primitive called a positional accumulator, introduced by Koppula, Lewko and Waters (STOC ’15) further supports dynamic updates of the hashed value. These tools, which are interesting in their own right, also serve as one of the main technical components in several recent works building advanced applications from indistinguishability obfuscation (iO). The prior constructions of SSB hashing and positional accumulators required fully homomorphic encryption (FHE) and iO respectively. In this work, we give new constructions of these tools based on well studied number-theoretic assumptions such as DDH, Phi-Hiding and DCR, as well as a general construction from lossy/injective functions.

Approximation and convergence of the intrinsic volume - Edelsbrunner, Herbert; Pausinger, Florian (Advances in Mathematics)
We introduce a modification of the classic notion of intrinsic volume using persistence moments of height functions. Evaluating the modified first intrinsic volume on digital approximations of a compact body with smoothly embedded boundary in Rn, we prove convergence to the first intrinsic volume of the body as the resolution of the approximation improves. We have weaker results for the other modified intrinsic volumes, proving they converge to the corresponding intrinsic volumes of the n-dimensional unit ball.

Guided search for hybrid systems based on coarse-grained space abstractions - Bogomolov, Sergiy; Donzé, Alexandre; Frehse, Goran; Grosu, Radu; Johnson, Taylor; Ladan, Hamed; Podelski, Andreas; Wehrle, Martin (International Journal on Software Tools for Technology Transfer)
Hybrid systems represent an important and powerful formalism for modeling real-world applications such as embedded systems. A verification tool like SpaceEx is based on the exploration of a symbolic search space (the region space). As a verification tool, it is typically optimized towards proving the absence of errors. In some settings, e.g., when the verification tool is employed in a feedback-directed design cycle, one would like to have the option to call a version that is optimized towards finding an error trajectory in the region space. A recent approach in this direction is based on guided search. Guided search relies on a cost function that indicates which states are promising to be explored, and preferably explores more promising states first. In this paper, we propose an abstraction-based cost function based on coarse-grained space abstractions for guiding the reachability analysis. For this purpose, a suitable abstraction technique that exploits the flexible granularity of modern reachability analysis algorithms is introduced. The new cost function is an effective extension of pattern database approaches that have been successfully applied in other areas. The approach has been implemented in the SpaceEx model checker. The evaluation shows its practical potential.

Optimal geospatial allocation of volunteers for crisis management - Pielorz, Jasmin; Lampert, Christoph
Volunteer supporters play an important role in modern crisis and disaster management. In the times of mobile Internet devices, help from thousands of volunteers can be requested within a short time span, thus relieving professional helpers from minor chores or geographically spread-out tasks. However, the simultaneous availability of many volunteers also poses new problems. In particular, the volunteer efforts must be well coordinated, or otherwise situations might emerge in which too many idle volunteers at one location become more of a burden than a relief to the professionals. In this work, we study the task of optimally assigning volunteers to selected locations, e.g. in order to perform regular measurements, to report on damage, or to distribute information or resources to the population in a crisis situation. We formulate the assignment tasks as an optimization problem and propose an effective and efficient solution procedure. Experiments on real data of the Team Österreich, consisting of over 36,000 Austrian volunteers, show the effectiveness and efficiency of our approach.

Square-free values of reducible polynomials - Browning, Timothy D; Booker, Andrew (Discrete Analysis)
We calculate admissible values of r such that a square-free polynomial with integer coefficients, no fixed prime divisor and irreducible factors of degree at most 3 takes infinitely many values that are a product of at most r distinct primes.

Is there a maximum mass for black holes in galactic nuclei? - Inayoshi, Kohei; Haiman, Zoltán (The Astrophysical Journal)
The largest observed supermassive black holes (SMBHs) have a mass of M_BH ~ 10^{10} M_sun, nearly independent of redshift, from the local (z~0) to the early (z>6) Universe. We suggest that the growth of SMBHs above a few 10^{10} M_sun is prevented by small-scale accretion physics, independent of the properties of their host galaxies or of cosmology. Growing more massive BHs requires a gas supply rate from galactic scales onto a nuclear region as high as >10^3 M_sun/yr. At such a high accretion rate, most of the gas converts to stars at large radii (~10-100 pc), well before reaching the BH. We adopt a simple model (Thompson et al. 2005) for a star-forming accretion disk, and find that the accretion rate in the sub-pc nuclear region is reduced to the smaller value of at most a few M_sun/yr. This prevents SMBHs from growing above ~10^{11} M_sun in the age of the Universe. Furthermore, once a SMBH reaches a sufficiently high mass, this rate falls below the critical value at which the accretion flow becomes advection dominated. Once this transition occurs, BH feeding can be suppressed by strong outflows and jets from hot gas near the BH. We find that the maximum SMBH mass, given by this transition, is between M_{BH,max} ~ (1-6) * 10^{10} M_sun, depending primarily on the efficiency of angular momentum transfer inside the galactic disk, and not on other properties of the host galaxy.